Role of corneal collagen fibrils in corneal disorders and related pathological conditions - Hong-Yan Zhou (International Journal of Ophthalmology, 2017)
The cornea is a soft tissue located at the front of the eye with the principal function of transmitting and refracting light rays to precisely sense visual information. Corneal shape, refraction, and stromal stiffness are to a large part determined by corneal fibrils, the arrangements of which define the corneal cells and their functional behaviour. However, the modality and alignment of native corneal collagen lamellae are altered in various corneal pathological states such as infection, injury, keratoconus, corneal scar formation, and keratoprosthesis. Furthermore, corneal recuperation after corneal pathological change is dependent on the balance of corneal collagen degradation and contraction. A thorough understanding of the characteristics of corneal collagen is thus necessary to develop viable therapies using the outcome of strategies using engineered corneas. In this review, we discuss the composition and distribution of corneal collagens as well as their degradation and contraction, and address the current status of corneal tissue engineering and the progress of corneal cross-linking.